Prospecting of popcorn inbred lines for nitrogen use efficiency and responsiveness - Pequeno de Souza, Yure; Teixeira do Amaral Junior, Antônio; de Oliveira, Fábio Tomaz; Khan, Shahid; Saltires Santos, Juliana; Kamphorst, Samuel Henrique (Revista Ceres, 2023)
Large amounts of nitrogen (N) fertilizers applied to maize cropping systems support high yields but cause adverse environmental impacts. The development of cultivars with higher N use efficiency is essential to maintain sustainable production. Thus, the present study aimed to select popcorn inbred lines efficient and responsive to N fertilization expressing high popping expansion. Fifty-one popcorn inbred lines from different origins were evaluated in the field under low and high N availability, arranged in a randomized complete block design with three replications. The two main traits of economic interest in the crop were evaluated: grain yield (GY) and popping expansion (PE). A joint analysis of variance was performed and a scatter plot was generated to classify the inbred lines regarding the response to the N use, focusing on GY. For PE, a Scott-Knott grouping of means was conducted. Within the panel of evaluated popcorn inbred lines, it was possible to identify sources of favorable alleles for nitrogen use efficiency and popcorn expansion, highlighting the inbred lines L205, L206, L217, and L395. These genotypes emerge as potential parents to be included in mating blocks for the development of hybrids and/or breeding populations with high nitrogen use efficiency and popping expansion.